Problem solving therapy for postpartum depression among Muslims postpartum women in Nigeria - Danasabe, Mahmood; Elias, Nadiyah (Society of Scientific Research and Education (SSRE), 2016)
Postpartum depression (PPD) is a common maternal physio psychosocial disorder and one of the most frequent emotional problem among Muslims population.It occurs at higher rate among postpartum mothers in the northern part of Nigeria.Depression impaired with individual’s problem solving ability.Problem solving therapy (PST) is effective in reducing postpartum depression (PPD), but the effectiveness has not been empirically tested among predominantly Muslims postpartum mothers and their problem solving abilities.This research tested the effectiveness of problem solving therapy in reducing postpartum depression (PPD) negative problem solving orientation (NPO) and increasing positive problem orientation (PPO) among Muslims postpartum mothers.This research employed quasi-experimental pre-posttest design.40 postpartum mothers from 18-47years were screened and conveniently sampled.They received six home-visits sessions of PST by post basic student nurses. Edinburgh postnatal depression scale (EPDS) measured (PPD) and social problem solving inventory revised form (SPSI-RF) measured (PPO) and (NPO).Results of the study revealed that PST is effective reducing the symptoms of PPD (pretest mean = 19.750; posttest mean = 17.505), NPO (pretest = 11. 4750: posttest = 10.5000) and PPO (pretest = 10.0750: posttest = 11.7250).This research indicates that PST can be feasible and used in treating postpartum depression and improving the positive orientation of the problem solving ability of postpartum depressed women.